Effects of Repetitive Peripheral Sensory Stimulation in the Subacute and Chronic Phases After Stroke: Study Protocol for a Pilot Randomized Trial - Kroth, Jéssica Borges; Handfas, Benjamim; Rodrigues, Glaucia; Zepeda, Francisco; Oliveira, Marco Aurélio; Wang, Danny J. J.; Azevedo Neto, Raymundo Machado de; Silva, Gisele Sampaio; Amaro, Edson; Sorinola, Isaac Olubunmi; Conforto, Adriana Bastos (Frontiers in Neurology, 2022)
Background: Repetitive peripheral nerve sensory stimulation (RPSS) is a potential add-on intervention to motor training for rehabilitation of upper limb paresis after stroke. Benefits of RPSS were reported in subjects in the chronic phase after stroke but there is limited information about the effects of this intervention within the first weeks or months. The primary goal of this study is to compare, in a head-to-head proof-of-principle study, the impact of a single session of suprasensory versus subsensory RPSS on upper limb motor performance and learning in subjects at different phases after stroke subacute and chronic phases and mild upper limb motor impairments after stroke. In addition, we will examine the effects of RPSS on brain perfusion, functional imaging activation and γ-Aminobutyric acid (GABA) levels. Subjects with mild upper limb motor impairments will be tested with MRI and clinical assessment either at an early (7 days-3 months post-stroke) or at a chronic (> 6 months) stage after stroke. Methods: In this multicenter, randomized, parallel-group, proof-of-principle clinical trial with blinded assessment of outcomes, we will compare the effects of one session of suprasensory or subsensory RPSS in patients with ischemic or hemorrhagic stroke and upper limb paresis:. Clinical assessment and MRI will be performed only once in each subject (either at an early or at a chronic stage). The primary outcome is the change in performance in the Jebsen-Taylor test. Secondary outcomes: hand strength, cerebral blood flow assessed with arterial spin labeling, changes in the BOLD effect in ipsilesional and contralesional primary motor cortex (M1) on left and right hemispheres assessed with functional magnetic imaging (fMRI) during a finger-tapping task performed with the paretic hand, and changes in GABA levels in ipsilesional and contralesional M1 evaluated with spectroscopy. The changes in outcomes will be compared in four groups: suprasensory, early; subsensory, early; suprasensory, chronic; subsensory, chronic. Discussion: The results of this study will be relevant to inform future clinical trials to tailor RPSS to patients more likely to benefit from this intervention. Trial registration: NCT03956407